Enhancement of Monopole Antenna Gain with Additional Vertical Wire Medium Structure - S. Kampeephat (2020)
© 2019 IEEE. In this paper, a monopole antenna with a new technique of metamaterial in term of the wire mediumstructure is used to present the possibility of the gain improvement of antenna. The wire mediumstructure, wire metamaterial, represents a large type of artificial electromagnetic structures that can be considered as dense arrays of aligned metal wires or rods embedded into dielectric matrices. In addition, we propose the dimensional structures of a monopole antenna and the wire medium in the present study have been designed and optimized at the operating frequency of 10 GHz. The antenna system consists of a monopole antenna that encircled with vertical wire medium structure. The enhancement of antenna gain of the wire mediumtechnique is to transfer the electromagnetic fields from a monopole through this vertical wire medium placed surrounding of the monopole, therefore, the phases of electromagnetic wave transmission are equal resulting in ultimate resonance. From our study, we found that the proper metamaterial structure, consistent with the radiation pattern, which is capable to enhance the gain of the antenna as the additional resonant circuit, exhibit bandgap characteristics at the operating frequency. The vertical wire medium structure, 3D volumetric structure, is utilized as the proper metamaterial in this paper that is designed at 10 GHz of the X-band operating frequency for microwave link applications. The advantages of this proposed technique are low profile, low cost, and lightweight. Ultimately, it is found that the proposed antenna resulting the gain at the operating frequency of 10 GHz is higher than the gain of a basic monopole antenna around 4 dBi with adding only one appropriated metamaterial on the vertical wire medium structure.